Phylloporia nouraguensis, an undescribed species on Myrtaceae from French Guiana - Decock, Cony (2013)
Phylloporia nouraguensis sp. nov. is described on the basis of several collections made in French Guiana. The species was found growing on living (or occasionally dead), small apical twigs of a species of Myrcia (Myrtaceae), in the so-called "low forest" covering the upper slopes of the Nouragues inselberg.